2014
DOI: 10.5423/ppj.nt.10.2013.0101
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Bacterial Wilt Caused by Ralstonia solanacearum Biovar 2 Race 1 on Tomato in Egypt

Abstract: This study aims to isolate and identify the causal pathogen of tomato bacterial wilt in Egypt. In 2008, tomato plants showing typical symptoms of bacterial wilt disease with no foliar yellowing were observed in Minia, Assiut and Sohag governorates, Egypt. When cut stems of symptomatic plants were submerged in water, whitish ooze was evident and longitudinal sections showed a brown discoloration in the vascular tissues. Bacteria were isolated on triphenyl tetrazolium chloride medium and fifteen isolates shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…A wilting score was recorded once a week for 4 weeks on a scale of 0 to 5, where 0 = no visible wilt, 1 = one leaf wilted, 2 = two or three leaves wilted, 3 = all except top leaves wilted, 4 = all leaves wilted, and 5 = dead (Wang et al 2000). Percentage of wilted plant (W) was calculated as described by Winstead and Kelman (1952) and Seleim et al (2014) using the formula W = [(Nt -Nh)/Nt] 9 100, where Nt is number of total plants and Nh is number of unwilted plants. W was arcsine square root-transformed for data normalization before QTL analysis using the PROC MIXED procedure of SAS (SAS 9.2, SAS Institute, Cary, USA).…”
Section: Caps Marker Designmentioning
confidence: 99%
“…A wilting score was recorded once a week for 4 weeks on a scale of 0 to 5, where 0 = no visible wilt, 1 = one leaf wilted, 2 = two or three leaves wilted, 3 = all except top leaves wilted, 4 = all leaves wilted, and 5 = dead (Wang et al 2000). Percentage of wilted plant (W) was calculated as described by Winstead and Kelman (1952) and Seleim et al (2014) using the formula W = [(Nt -Nh)/Nt] 9 100, where Nt is number of total plants and Nh is number of unwilted plants. W was arcsine square root-transformed for data normalization before QTL analysis using the PROC MIXED procedure of SAS (SAS 9.2, SAS Institute, Cary, USA).…”
Section: Caps Marker Designmentioning
confidence: 99%
“…5 ml of TZC solution filter sterilized was added to the autoclaved medium to give final concentration of 0.005%) according to the procedure of Seleim, et al [12]. The plates were incubated at 28 o C ± 2°C for 24-48 hr.…”
mentioning
confidence: 99%
“…H 2 S production was noticed by the appearance of black precipitation. Seleim et al (2014) also found positive motility for all R. solanacearum isolates from wilt infected tomato plants. In the biochemical test, R. solanacearum strain BD isolated from wilt disease of papaya showed positivity to methyl red and Kovac oxidase which is confirmatory with the findings of Zhang et al (2011) .…”
Section: Discussionmentioning
confidence: 75%